Management of delayed gastric conduit emptying after esophagectomy - Zhang, Rusi; Zhang, Lanjun (Journal of Thoracic Disease, 2018)
Delayed gastric conduit emptying (DGE) is a common complication after esophagectomy. Currently, pyloric interventions are the major prevention and treatment for DGE. In this review, we attempt to evaluate the clinical effect and safety of different pyloric interventions in esophagectomy patients. Moreover, other important management of DGE, including size of esophageal substitute, erythromycin and nasogastric tube (NGT) will also be discussed.